"Progressive" Criminalization? A Sociological and Criminological Analysis Based on the German "No Means No" Provision. Issue 5 (August 2021) - Kölbel, Ralf
Abstract: The "no means no" model has been applied in Germany since November 10, 2016. Its introduction has considerably extended the scope of criminalized forms of sexual interaction. This Article examines the criminal policy discourse that gave rise to it and the question of whether the new provisions have led to the changes in the practices of criminal prosecution proclaimed in advance. The results will be critically assessed. The new legislation relating to sexual offenses was also shaped on the initiative of groups perceiving themselves as emancipatory, and in the understanding of these groups, the "no means no" provision acts as "progressive" criminalization. Yet, aside from the fact that the associated expectations have hardly been met as of yet, this movement would have to resolve an essential question: Is penal law compatible with a "progressive" social policy they claim to stand for at all, and if so, what conditions does it have to meet?